Guillain Barré with respiratory compromise, a clinical case of pediatric emergency - Vilca Rabanal, Eliana; Moscoso Blanco, Milagros Yohanna; Castillo Zamora, Luz Victoria; Ponti, Liliana Elba (Salud Integral y Comunitaria, 2025)
Clinical case of a 2-year-old boy diagnosed with severe respiratory failure and Guillain-Barré syndrome, with the objective of managing a care plan to restore respiratory distress. Using the Marjory Gordon’s health patterns assesment, 4 NANDA-I (NANDA Internationa taxonomy) diagnoses were found, prioritized and analized according to the OPT model. The care plan and execution was based on NOC and NIC taxonomy. The care plan successfully achieved airway stability and provided quality care.